Relationship between job involvement, perceived organizational support, and organizational commitment with job insecurity: A systematic literature review - Hngoi, Chin Ling; Abdullah, Nurul-Azza; Wan Sulaiman, Wan Shahrazad; Zaiedy Nor, Norshaffika Izzaty (Frontiers in Psychology, 2023)
This manuscript aims to review the literature on the relationship between job insecurity and job involvement, perceived organizational support, organizational commitment, and positional characteristics. The definition and conceptualization of the variables are discussed for clarity. This systematic review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to summarize and review 19 articles on job insecurity. The result shows gaps in the relationship between job involvement and organizational commitment, yielding no result from the search. This review identified implications and areas for future research on the topic. It also found evidence supporting the need to further investigate the antecedents and consequences of job insecurity in order to improve productivity and reduce attrition.